One Hundred Fifty Liver Transplants at a New Program in the Modern Era: The University of Mississippi Experience. Issue 9 (September 2019) - Curtis, Kyle; Anderson, Christopher; Seawright, Ashley; Koller, Felicitas; Wynn, James; Henderson, Dean; Earl, Truman
From 1991 to 2013, Mississippi was without liver transplant services. In 2013, a new liver transplant program was established at the University of Mississippi Medical Center. Here, we describe our experience with the first 150 transplants over a 4.5-year period. This study is a review of 147 patients who underwent the first 150 liver transplants at the University of Mississippi Medical Center between March 5, 2013, and January 4, 2018. There were no exclusion criteria for this study. Donor, recipient, and outcome variables were analyzed. Recipients were 46% female and 74% white. Age at the time of transplant was 57 [IQR 49–63]. BMI at transplant was 30 [IQR 25–35]. Thirty per cent of transplants were for alcoholic cirrhosis, 25% non-alcoholic steatohepatitis, 24% hepatitis C, and 12% cholestatic. Mean model for end-stage liver disease (MELD) at the time of transplant was 20 [95% confidence interval 19–21] and MELD-Na was 22 [95% confidence interval 20–23]. One-year patient- and graft survival were 89% and 87%, respectively, which were as expected based on Scientific Registry of Transplant Recipient reports after risk adjustment. The data published here verifies it is possible to establish a new liver transplant center in an underserved area previously lacking comprehensive liver care and to achieve results similar to other high-volume centers across the country.